Rethinking government and its economy with Giorgio Agamben: The homo sacer in alternative entrepreneurship. Issue 5 (September 2020) - Redmalm, David; Skoglund, Annika
Giorgio Agamben argues in The Kingdom and the Glory (2011) that a theological remnant has survived since the medieval period that today makes it impossible to think of government and economy, or ethico-political questions and the administration of a society's resources, separately. This conflation can be recognized in today's growing trend of alternative entrepreneurial ventures that aim to merge social and economic value creation in response to shrinking welfare states. 'Alternative entrepreneurship' merges organizational goals and values with those of their members with the aim to increase innovation and productivity, and to spur social change. Rather than asking if and how alternative entrepreneurship can solve social problems, the present article contributes to a sociological understanding of the special kind of humanism embedded in these ventures. Drawing on Agamben's work, this article theorizes the process that enables the conflation of personal and organizational values, and of 'government and its economy'. The contribution is based on an ethnographic study of an IT company, founded in Hungary around 2010, and its engagement in the Budapest Pride Parade, in a Roma settlement, and in a mission to help Syrian refugees. Following Agamben, we think through these interventions as 'zones of indistinction' where organizational boundaries are dissolved, where contradictory values are conflated, and where the participants are positioned as homines sacri whose humanity is at stake. This article shows how the encounters within these zones enable a merging of idealism and economic gain, turning the company itself into a zone of indistinction.